Comparison of Surgical Outcomes Between Separation Surgery and Piecemeal Spondylectomy for Spinal Metastasis: A Retrospective Analysis - Xu, Lun; Huang, Wending; Cai, Weiluo; Sun, ZhengWang; Fang, Meng; Ji, Yingzheng; Wang, Shuoer; Zhang, Jianing; Hu, Tu; Cheng, Mo; Yan, Wangjun (Frontiers in Surgery, 2021)
Objective: This study aimed to compare the outcomes between piecemeal spondylectomy and separation surgery for patients with spinal metastasis. Summary of Background Data: Piecemeal spondylectomy and separation surgery are two widely-used treatment options for spinal metastasis. However, no studies have compared the surgical outcomes between both treatment modalities. Methods: Patients with spinal metastasis who underwent piecemeal spondylectomy or separation surgery between August 2017 and April 2020 at our spine center were recruited. Demographic, preoperative, perioperative, and follow-up data were collected and analyzed. Kaplan–Meier analysis and the log-rank test were used to analyze overall survival (OS) and progression-free survival (PFS) in patients with spinal metastasis. Results: Overall, 26 patients were treated with piecemeal spondylectomy, and 29 underwent separation surgery with postoperative stereotactic radiosurgery. Both groups showed significant postoperative improvements in neurological status. The piecemeal spondylectomy group had significantly more blood loss (1784.62 ± 833.64 mL vs. 1165.52 ± 307.38 mL) and required longer operative time (4.76 ± 0.93 h vs. 3.73 ± 1.15 h) than the separation surgery group. No significant difference in OS was found between the groups (P = 0.064); however, patients in the separation surgery group experienced less local recurrence than those in the piecemeal spondylectomy group (P = 0.0014). Notably, significant differences were detected in the development of complications between the groups (P = 0.029). Conclusion: Separation surgery led to less blood loss and reduced complications and had shorter operation time than piecemeal spondylectomy. Although no significant differences were found in OS between the groups, separation surgery was associated with better PFS compared with piecemeal spondylectomy. These findings suggest that separation surgery has some advantages over piecemeal spondylectomy for patients with spinal metastatic disease.